Kasos ir dvylikapirštės žarnos sužalojimų gydymas - Lappäniemi, Ari (Lietuvos chirurgija, 2007)
Ari Lappäniemi Meilahti Hospital, Department of Surgery, University of Helsinki, Haartmaninkatu 4, P.O. Box 340, FIN-00029 HUS, Finland E-mail: ari.leppaniemi@hus.fi Pancreatic and duodenal injuries are rare and, excluding patients with devastating injuries to the pancreaticoduodenal complex and adjacent vascular injuries, can be managed successfully with adequate and determinate exposure during explorative laparotomy, simple surgical procedures, and sound surgical judgment adapted to the demands of the circumstances and the skills of the operating surgeon. Nevertheless, more complex repair techniques, such as distal pancreaticojejunostomy or pyloric exclusion, may be needed for optimal results in more demanding injuries. Although mortality specifically related to the pancreatic or duodenal injury itself is relatively low, postoperative complications are frequent and often associated with delayed diagnosis and treatment. Key words: abdominal trauma, pancreas, duodenum, pancreaticoduodenal injuries